Research on Factors Affecting the Career Choice Decision of High School Students in Thai Nguyen Province - Tuan, Bui Ngoc (Jurnal Teknologi Informasi dan Pendidikan, 2024)
This study evaluates factors influencing career choice decisions among high school students in Thai Nguyen province through statistical analysis. Results indicate that crucial factors affecting these decisions include labor market needs, career counseling, family influence, university factors, and personal preferences. Exploratory factor analysis identifies 5 significant factors, explaining 73.68% of data variance. Strong positive correlations are observed between career decisions and factors such as labor market needs, career counseling, family, university factors, and personal preferences. Additionally, a linear regression model predicts that labor market demand, career counseling, and university factors positively and significantly influence career choices, while personal and family influences show weaker correlations. Practical implications of this research include assisting educational institutions, families, and students in comprehending career decisions and formulating effective support strategies.